2015 개정 교육과정 기반 중학교 3학년 영어 교과서 쓰기 활동 분석 - 조수현; 맹은경 (현대영어교육, 2022)
Writing is an essential and complex skill that does not develop naturally. In an EFL context, it is necessary for L2 teachers to provide adequate practice and instruction to students. English textbooks are essential foundation for teaching in the classroom. Thus, this study examined the effectiveness of writing activities in 9th grade English textbooks. Five governmentauthorized middle school English textbooks widely used in Gyeonggi Province were selected and analyzed. Validity of writing activities in textbooks was analyzed based on writing achievement standards of the 2015 revised national English curriculum, writing task type, and genre. Results are as follows. First, writing activities in 9th grade middle school English textbooks did not fully meet writing achievement standards. Most writing activities were implemented based on standards [9E04-01] and [9E04-2]. Second, the most common type of writing activity in those textbooks was controlled writing (63.6%), followed by guided writing (21.1%) and free writing (9.3%). Third, although various types of genres were incorporated in writing activities, more than half of writing activities were expository writing (43%) and journal/letter (25%). These findings suggest that L2 teachers need to provide various types of writing activities to help students achieve writing standards and enhance their writing abilities.
Keywords: 영어 교과서 분석; 쓰기 활동 유형; 성취기준; 장르중심접근법; English textbook analysis; writing activity types; achievement standard; genre approach